A study on music therapy aimed at psychological trauma recovery for bereaved families driven by artificial intelligence - Wang, Zixi; Guan, Xin; Li, Enhui; Dong, Bo (Frontiers in Psychology, 2024)
This study aims to explore the effectiveness of music therapy in repairing psychological trauma in bereaved families. Firstly, an analysis of the current situation of bereaved families is conducted.Secondly, the contents of research design and participant recruitment are elaborated. Finally, based on an optimized Long Short-Term Memory (LSTM) network, a model tailored to the characteristics of music therapy data is constructed. The specific operations of music therapy process, as well as the detailed settings of the experimental group and the control group, are described. The results indicate that compared to other models, the performance of the model proposed in this study is good (with accuracy, precision, recall, and F1-score being 0.88, 0.89, 0.87, and 0.88, respectively). The comparison between the treatment effects predicted by the model and the improvement characterized by the Self-Reporting Inventory-90 (SCL-90) scale shows that the model has a certain level of accuracy and reliability, capturing the approximate trend of treatment effects. Further analysis comparing the improvement in psychological issues between the experimental group and the control group validates the advantages of using the model proposed in this study for music therapy in the experimental group. Participants numbered 2, 6, and 8 in the experimental group showed treatment improvement rates of 67.21%, 71.45%, and 76.67%, respectively. The initial psychological state has the greatest impact on treatment outcomes, with a regression coefficient of 0.45, indicating that individuals with poorer initial psychological states benefit more from the treatment. The economic background also significantly affects treatment results, with higher improvements observed among participants with higher incomes (p<0.00001). Through comparative analysis of the treatment effects between the experimental group and the control group, patients in the experimental group using the model proposed in this study for music therapy demonstrated better improvement in psychological health issues. This study provides new ideas and methods for the application of music therapy in